2015
DOI: 10.3748/wjg.v21.i12.3492
|View full text |Cite
|
Sign up to set email alerts
|

Long-chain acyl-CoA synthetase in fatty acid metabolism involved in liver and other diseases: An update

Abstract: Long-chain acyl-CoA synthetase (ACSL) family members include five different ACSL isoforms, each encoded by a separate gene and have multiple spliced variants. ACSLs on endoplasmic reticulum and mitochondrial outer membrance catalyze fatty acids with chain lengths from 12 to 20 carbon atoms to form acyl-CoAs, which are lipid metabolic intermediates and involved in fatty acid metabolism, membrane modifications and various physiological processes. Gain- or loss-of-function studies have shown that the expression o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
112
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 172 publications
(119 citation statements)
references
References 51 publications
6
112
0
1
Order By: Relevance
“…This finding is highlighted by a study that found that the pan-ACSL inhibitor, Triacsin C, preferentially inhibited TAG synthesis and did not affect FAO (71). Furthermore, although both ACSL1 and ACSL5 have been reported to localize at the mitochondrial and the LD membranes (72) and ACSL1 has been reported to up-regulate genes involved in FAO (73), they do not affect the FAO rate (74,75). Based on our data, ACSLs promote lipid storage in LDs (Fig.…”
Section: Low-lipid Content Favors Promigratory Phenotype Of Breast Casupporting
confidence: 78%
“…This finding is highlighted by a study that found that the pan-ACSL inhibitor, Triacsin C, preferentially inhibited TAG synthesis and did not affect FAO (71). Furthermore, although both ACSL1 and ACSL5 have been reported to localize at the mitochondrial and the LD membranes (72) and ACSL1 has been reported to up-regulate genes involved in FAO (73), they do not affect the FAO rate (74,75). Based on our data, ACSLs promote lipid storage in LDs (Fig.…”
Section: Low-lipid Content Favors Promigratory Phenotype Of Breast Casupporting
confidence: 78%
“…Acyl-CoA synthetases are classified based on the carbon chain length of their preferred acyl group. Octanoic acid C8 is the substrate for medium-chain acyl-CoA synthetase ACSM , and 18 carbon length fatty acids such as stearic acid, oleic acid, linoleic acid, and α-linolenic acid, are substrates for long-chain acyl-CoA synthetase 35,36 .…”
Section: Discussionmentioning
confidence: 99%
“…Dysfunction of these enzymes can lead to many metabolic diseases, such as those related to metabolic syndrome, fatty liver and neurological disorders (Yan et al . ). In humans, a defect in the activation of the fatty acids by ACSL in the muscle of black women may contribute to the maintenance of obesity (Privette et al .…”
Section: Introductionmentioning
confidence: 97%